2014
DOI: 10.1371/journal.pgen.1004220
|View full text |Cite
|
Sign up to set email alerts
|

Dying Cells Protect Survivors from Radiation-Induced Cell Death in Drosophila

Abstract: We report a phenomenon wherein induction of cell death by a variety of means in wing imaginal discs of Drosophila larvae resulted in the activation of an anti-apoptotic microRNA, bantam. Cells in the vicinity of dying cells also become harder to kill by ionizing radiation (IR)-induced apoptosis. Both ban activation and increased protection from IR required receptor tyrosine kinase Tie, which we identified in a genetic screen for modifiers of ban. tie mutants were hypersensitive to radiation, and radiation sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 53 publications
0
42
2
Order By: Relevance
“…It should be pointed out, however, that apoptotic cells have also been shown to induce increased survival of adjacent cells (Bilak et al, 2014). This process depends on activation of the antiapoptosis microRNA Bantam and the receptor tyrosine kinase Tie.…”
Section: Apoptosis-induced Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…It should be pointed out, however, that apoptotic cells have also been shown to induce increased survival of adjacent cells (Bilak et al, 2014). This process depends on activation of the antiapoptosis microRNA Bantam and the receptor tyrosine kinase Tie.…”
Section: Apoptosis-induced Apoptosismentioning
confidence: 99%
“…This process depends on activation of the antiapoptosis microRNA Bantam and the receptor tyrosine kinase Tie. In addition, the Drosophila PDGF/VGF-like protein Pvf1 was identified as a potential signal produced by apoptotic cells and is involved in Tie activation (Bilak et al, 2014). The exact mechanism by which apoptotic signaling modulates cell survival remains to be elucidated.…”
Section: Apoptosis-induced Apoptosismentioning
confidence: 99%
“…Interestingly, ''genuine'' dying cells confer protection on nearby surviving cells, which become harder to kill through a mechanism that involves the micro-RNA bantam. 57 Wound closure. Because the damage that stimulates CP is scattered throughout the tissue, there are no large discontinuities of the epithelium that require closing.…”
Section: Compensatory Proliferationmentioning
confidence: 99%
“…57 This screen sought mutants in which the living cells failed to carry out enough CP to replace the dying cells. Many mutations isolated affect genes that are also required for normal developmental growth, but CP was particularly sensitive to their loss.…”
Section: Compensatory Proliferationmentioning
confidence: 99%
“…Additionally, bantam null animals were exceptionally susceptible to ionizing radiation, exhibiting increased apoptosis. However, follow-up studies by the same group revealed the surprising finding that when apoptosis is limited to a specific domain, the increase in bantam , and thus the antiapoptotic effect, was nonautonomous (Bilak, Uyetake, & Su, 2014). These authors found that AiDR, which they termed the “Mahakali” effect, was mediated by the receptor tyrosine kinase Tie on the surviving cell, and the apoptosis-dependent production of the Pvf1 ligand.…”
Section: Apoptotic Cells Directly Influence Tissue Homeostasis Andmentioning
confidence: 99%